Optimization Of The State’s Role In Facing The 2019 Coronavirus Disease Pandemic From The Perspective Of Emergency Constitutional Law - Firman Freaddy Busroh; Fatria Khairo (IHSA Institute, 2022)
Since the end of 2019, WHO has determined that Covid-19 is a pandemic that attacks the world. This pandemic resulted in a health emergency, which had a bad impact on various sectors, including the financial sector, so the economic situation became unstable. The purpose of this research is to see how the role of the state in overcoming the problems of the Covid-19 pandemic from the perspective of emergency constitutional law. This research will be carried out using statutory, conceptual, and comparative approaches. The data used in this study came from the results of a literature study. The results of this research will be in the face of the covid-19 pandemic, the application of emergency constitutional law is a responsive and progressive step. This function is to provide guarantees and achieve the ideals of the rule of law, which is to provide protection and welfare for the community as the highest law in a country.